Woman as a Work of Art. Journalistic Opinions from the Interwar Epoch - Teodorașcu, Fănel (Acta Universitatis Danubius. Communicatio, 2024)
Among the novelties brought by the interwar years to the Romanian society, there was the belief that any woman can be beautiful. The problem of lacking natural beauty had become something easy to solve, by using a few cosmetic products, by frequently visiting the beauty centers and by replacing old clothes with some new en vogue ones, according to the latest fashion of the European cities. Those women, who were already beautiful, would have become even more beautiful, if they had followed the beauty secrets, secrets which could be discovered in the columns of the newspapers and magazines. Some men from that very epoch even stated that some women could be considered real works of art. This is exactly what interests us mostly in the current research. Thus, we aimed at analysing what was written in some Romanian interwar newspapers in connection to the idea that woman’s knowledge of being beautiful can be considered a form of art.